A comparative study of guided vs. pure self-treatment for premature ejaculation. Issue 3 (3rd July 2018) - Kempeneers, Philippe; Andrianne, Robert; Cuddy, Marion; Georis, Isabelle; Longrée, Quentin; Blairy, Sylvie
ABSTRACT: Self-treatments have previously shown some efficacy in treating premature ejaculation (PE). It has been hypothesized that adding professional support to cognitive-behaviour bibliotherapy could improve self-treatment outcomes. Therefore, the aim of this study was to compare treatment outcomes for participants with PE who used bibliotherapy alone (pure self-treatment) versus those who used the bibliotherapy with brief support from a health professional (guided self-treatment). Health professionals were not experienced sex therapists, but had attended a short training session in order to equip them to support the self-help process. In total, 135 men reporting difficulties with PE were recruited between February and June 2013. Seventy-one (52.59%) completed the protocol: 37 in the pure self-treatment condition, 34 in the guided self-treatment condition. Thirty-five participants (50%) met criteria for ISSM definition of lifelong PE, 14 (20%) for acquired PE, and 22 (30%) presented other forms of PE complaints. At 4–8 months post-treatment, improvements were found in both groups and in each subtype of PE on self-reported measures of sexual functioning and sexual cognitions. Univariate analyses indicated slightly greater treatment effects in the guided self-treatment group, but multivariate tests failed to identify a significant effect of therapist support. These mixed findings raise questions regarding the amount and quality of therapist input used in this study, and also about a possible ceiling effect of cognitive-behaviour therapy for PE.